Integrating Pancasila Values in the Arab Context for Arabic Language Education Students - Wartinah Wartinah; Sabarudin Sabarudin; Khoirul Anam; Adhi Setiyawan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Abstract This study aims to analyze the integration of Pancasila values within the context of Arabness among students in the Arabic Language Education Study Program (PBA), an academic space synonymous with intense interaction with Arabic language, culture, and texts. Through a qualitative approach with a case study design, this research delves into how students interpret, negotiate, and implement Pancasila values within the dynamics of learning rich with Middle Eastern cultural and religious content. The findings indicate that the integration of Pancasila values is still symbolic and normative, as evidenced by the tendency of both lecturers and students to associate the principles of Pancasila with verses or hadiths without critical recontextualization. This condition makes students vulnerable to experiencing epistemological tension, especially when facing Arab socio-cultural practices that are not entirely aligned with the principles of democracy, equality, and social justice in Pancasila. The lack of explicit pedagogical strategies in connecting these two value systems also contributes to the emergence of ambiguity in national identity. Nevertheless, this study identifies opportunities for integration through a critical recontextualization approach, a historical-cultural reading of Arab texts, and providing space for reflective dialogue in learning. This approach not only allows for the harmonization of Arab values with Pancasila but also contributes to strengthening national character and intercultural competence among PBA students.